Manufacturing method of LGPS type solid electrolyte
By sintering LGPS solid electrolytes in a nitrogen atmosphere with controlled moisture levels, the method addresses high production costs and enhances ionic conductivity, producing electrolytes suitable for all-solid-state batteries.
Patent Information
- Application Number
- JP2021049790
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-24
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-03-24
AI Technical Summary
The production of LGPS type solid electrolytes is hindered by high costs due to the use of large amounts of inert gases like argon, and they are prone to reduced ionic conductivity from moisture and oxygen exposure.
The production method involves sintering the LGPS solid electrolyte precursor in a nitrogen gas atmosphere with a controlled moisture content between 100 ppm and 300 ppm, specifically between 120 ppm and 295 ppm, to enhance ionic conductivity.
This method reduces production costs and achieves LGPS type solid electrolytes with ionic conductivities of 3.2 mS/cm or more at 25°C for Ge-containing electrolytes and 2.8 mS/cm or more at 25°C for Sn-containing electrolytes, suitable for all-solid-state batteries.
Smart Images

Figure 0007615815000001 
Figure 0007615815000002 
Figure 0007615815000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a LGPS type solid electrolyte. The LGPS type solid electrolyte refers to a solid electrolyte having a specific crystal structure containing Li, P, and S, and examples thereof include solid electrolytes containing Li, M (M is one or more elements selected from the group consisting of Ge, Si, and Sn), P, and S. [Background technology]
[0002] In recent years, the demand for lithium-ion secondary batteries has been increasing for applications such as mobile information terminals, mobile electronic devices, electric vehicles, hybrid electric vehicles, and stationary power storage systems. However, current lithium-ion secondary batteries use flammable organic solvents as electrolytes, and require a strong exterior to prevent the organic solvent from leaking. In addition, there are restrictions on the structure of devices, such as portable personal computers, which must be designed to protect against the risk of electrolyte leakage.
[0003] Furthermore, their applications are expanding to mobile objects such as automobiles and airplanes, and large capacity is required for stationary lithium-ion secondary batteries. Under these circumstances, there is a tendency to place more importance on safety than ever before, and efforts are being made to develop all-solid-state lithium-ion secondary batteries that do not use harmful substances such as organic solvents.
[0004] For example, the use of oxides, phosphate compounds, organic polymers, sulfides, and the like as solid electrolytes in all-solid-state lithium ion secondary batteries has been considered. Among these solid electrolytes, sulfides have the characteristics of high ionic conductivity, being relatively soft and easily forming solid-solid interfaces. They are also stable against active materials, and development is underway as a practical solid electrolyte.
[0005] Among sulfide solid electrolytes, there is an LGPS-type solid electrolyte with a specific crystal structure (Non-Patent Document 1 and Patent Document 1). Among sulfide solid electrolytes, the LGPS-type solid electrolyte has extremely high ionic conductivity and can operate stably from low temperatures of -30°C to high temperatures of 100°C, and there are high expectations for its practical application.
[0006] LGPS-type solid electrolytes react easily with moisture and oxygen to generate hydroxides and oxides, which causes a decrease in ionic conductivity, so all manufacturing processes are carried out in an environment that does not contain moisture or oxygen. Non-Patent Document 2 shows that LGPS-type solid electrolytes with high ionic conductivity can be manufactured by sintering while flowing argon gas. However, when considering industrial manufacturing, a huge amount of gas is used, and the use of argon gas raises the problem of high production costs. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 3125507 [Non-patent literature]
[0008] [Non-Patent Document 1] Nature Energy 1, Article number: 16030 (2016) [Non-Patent Document 2] Journal of Power Source 473 (2020) 228524 Summary of the Invention [Problem to be solved by the invention]
[0009] Under these circumstances, it is desired to provide a method for producing an LGPS-type solid electrolyte having high ionic conductivity while suppressing production costs. [Means for solving the problem]
[0010] Therefore, the present inventors have conducted intensive research in view of the above problems, and have discovered that an LGPS-type solid electrolyte exhibiting high ionic conductivity can be produced by synthesizing the LGPS-type solid electrolyte and firing it in a nitrogen gas atmosphere containing moisture in the range of more than 100 ppm and not more than 300 ppm.
[0011] That is, the present invention is as follows. <1> The method for producing an LGPS type solid electrolyte is characterized by including a step of firing an LGPS type solid electrolyte precursor in a nitrogen gas atmosphere containing moisture in the range of more than 100 ppm and not more than 300 ppm. <2> The LGPS-type solid electrolyte has peaks at least at 2θ=20.18°±0.50°, 20.44°±0.50°, 26.96°±0.50°, and 29.58°±0.50° in X-ray diffraction (CuKα: λ=1.5405 Å). <1> This is a method for producing the LGPS type solid electrolyte described in the above. <3> The firing temperature is 200° C. to 700° C. <1> or <2> This is a method for producing the LGPS type solid electrolyte described in the above. <4> The LGPS type solid electrolyte contains Ge and has an ionic conductivity of 3.2 mS / cm or more at 25° C. <1> from <3> 1 is a method for producing the LGPS type solid electrolyte according to any one of the above items. <5> The LGPS type solid electrolyte contains Sn and has an ionic conductivity of 2.8 mS / cm or more at 25° C. <1> from <3> 1 is a method for producing the LGPS type solid electrolyte according to any one of the above items. Effect of the Invention
[0012] According to the present invention, it is possible to provide a method for producing an LGPS-type solid electrolyte having high ionic conductivity while suppressing production costs, and also to provide a molded body obtained by hot molding the LGPS-type solid electrolyte, and an all-solid-state battery including the LGPS-type solid electrolyte. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic diagram showing the crystal structure of an LGPS-type solid electrolyte according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of an all-solid-state battery according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a graph showing the results of measuring the ionic conductivity of the Ge-type LGPS solid electrolytes obtained in Examples 1 to 4 and Comparative Example 1. [Figure 4] FIG. 4 is a graph showing the results of measuring the ionic conductivity of the Sn-type LGPS solid electrolytes obtained in Examples 5 to 8 and Comparative Example 2. [Diagram 5] FIG. 5 is a graph showing the results of X-ray diffraction measurement of the Ge-type LGPS solid electrolytes obtained in Examples 1 to 4 and Comparative Example 1. [Figure 6] FIG. 6 is a graph showing the results of X-ray diffraction measurement of the Sn-type LGPS solid electrolytes obtained in Examples 5 to 8 and Comparative Example 2. [Figure 7] FIG. 7 is a schematic diagram of a heating vessel for carrying out a firing step in a method for producing an LGPS type solid electrolyte according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described in detail below. Note that the materials and configurations described below do not limit the present invention, and various modifications can be made within the scope of the present invention.
[0015] In this specification, the LGPS type solid electrolyte refers to a solid electrolyte containing Li, P, and S and having a specific crystal structure, and examples thereof include solid electrolytes containing Li, M (M is one or more elements selected from the group consisting of Ge, Si, and Sn), P, and S.
[0016] As shown in Fig. 1, the crystal structure of the LGPS-type solid electrolyte has an octahedron O composed of Li and S elements, a tetrahedron T1 composed of one or more elements selected from the group consisting of P, Ge, Si, and Sn and S elements, and a tetrahedron T2 composed of P and S elements. The tetrahedron T1 and the octahedron O share an edge, and the tetrahedron T2 and the octahedron O share a vertex.
[0017] The LGPS-type solid electrolyte has peaks at positions of at least 2θ = 20.18° ± 0.50°, 20.44° ± 0.50°, 26.96° ± 0.50°, and 29.58° ± 0.50° in X-ray diffraction (CuKα: λ = 1.5405 Å).
[0018] The LGPS-type solid electrolyte of the present invention is manufactured by mixing raw materials to a desired molar ratio, reacting while pulverizing to produce an LGPS-type solid electrolyte precursor, and firing the produced LGPS-type solid electrolyte precursor.
[0019] <Manufacture of LGPS-Type Solid Electrolyte Precursor> The LGPS-type solid electrolyte precursor, which is the object of the manufacturing method of the LGPS-type solid electrolyte of the present invention, can be manufactured by known methods such as the mechanical milling method described in Japanese Patent No. 5527673 and the liquid phase synthesis method described in International Publication No. WO2019 / 044517.
[0020] Mechanical Milling Taking an example of the mechanical milling method, after mixing powders of Li2S, P2S5, and MS2 (M is one or more elements selected from the group consisting of Ge, Si, and Sn), a pulverization and mixing treatment is performed using a planetary ball mill or the like to obtain an LGPS-type solid electrolyte precursor. The feature of the mechanical milling method lies in performing composition homogenization and amorphization by applying strong mechanical energy.
[0021] Liquid Phase Synthesis As an example of the liquid phase synthesis method, Li2S and P2S5 are reacted in an organic solvent such as acetonitrile or tetrahydrofuran to dissolve the resulting solution, and powders of Li2S and MS2 (M is one or more elements selected from the group consisting of Ge, Si, and Sn) are added to the solution to obtain a suspension. Next, the organic solvent is distilled off to obtain a LGPS-type solid electrolyte precursor. The liquid phase synthesis method is characterized in that the composition is homogenized and amorphous by reacting and dissolving part or all of the raw materials in the organic solvent.
[0022] <Firing> The heating temperature varies depending on the type, and for those containing Ge, Si or Sn, it is usually preferably in the range of 200 to 700° C., more preferably in the range of 350 to 650° C., and particularly preferably in the range of 400 to 600° C. If the temperature is lower than the above range, it is difficult to produce the desired crystals, while if the temperature is higher than the above range, crystals other than the desired ones may be produced.
[0023] Although the heating time varies slightly depending on the heating temperature, a heating time in the range of 0.1 to 24 hours is usually sufficient for crystallization. Heating at a high temperature for a long period of time exceeding the above range is not preferable because there is a concern that the LGPS-type solid electrolyte may be altered.
[0024] In the present invention, the firing is performed under a nitrogen gas atmosphere from the viewpoint of suppressing production costs. Considering industrial production, a huge amount of gas is used, so using an inert gas such as helium gas or argon gas instead of nitrogen gas is not preferable from the viewpoint of production costs, and it is preferable to use inexpensive nitrogen gas. Generally, it is considered preferable to use inert gas with a low moisture content for firing, and high-purity gas with a moisture content of less than 5 ppm has been used. Even when standard grade inert gas is used, the moisture content is often less than 10 ppm.
[0025] According to the inventors' research, it is believed that when the nitrogen gas used contains a small amount of moisture, the moisture reacts with the surface of the LGPS-type solid electrolyte, and oxygen is taken into the structure. This changes the size of the tunnel through which the Li ions in the crystal pass to a size that is more conductive, improving ion conductivity. However, if the amount of water contained in the nitrogen gas is too much, it exceeds the solid solubility range of oxygen, and an impurity layer is formed, which is thought to reduce ionic conductivity. Therefore, the amount of water contained in the nitrogen gas should not be too much or too little. When the LGPS type solid electrolyte obtained by the present invention contains Ge, the ionic conductivity at 25° C. is preferably 3.2 mS / cm or more, and more preferably 3.5 mS / cm or more. When the LGPS type solid electrolyte obtained by the present invention contains Sn, the ionic conductivity at 25° C. is preferably 2.8 mS / cm or more, and more preferably 2.9 mS / cm or more. In the present invention, the method for measuring the ionic conductivity can be the method described in the examples below.
[0026] In the present invention, the amount of water contained in the nitrogen gas needs to be more than 100 ppm and not more than 300 ppm. It is preferably between 120 ppm and 295 ppm. It is particularly preferably between 140 ppm and 290 ppm. By making the amount of water contained in the nitrogen gas more than 100 ppm and not more than 300 ppm, it is possible to obtain a LGPS solid electrolyte having high ionic conductivity. A method for adjusting the amount of moisture contained in nitrogen gas to more than 100 ppm and not more than 300 ppm is, for example, to prepare nitrogen gas with a moisture content of 100 ppm or less and nitrogen gas with a moisture content of 300 ppm or more and mix them in any ratio. A dew point meter can be used to measure the amount of moisture contained in nitrogen gas.
[0027] 7 is a schematic diagram of an example of a heating vessel in which a firing step is performed. The heating vessel 11 has a glass inner cylinder 12 and a glass outer cylinder 13. A LGPS-type solid electrolyte precursor 14 is placed in the glass inner cylinder 12. The heating vessel 11 is sealed with a stopper (not shown), and nitrogen gas is introduced and discharged through a branch pipe. A thermocouple 15 is provided to measure the temperature inside the glass inner cylinder 12. Here, when the heating vessel 11 is heated using a tubular furnace 16, the LGPS-type solid electrolyte precursor 14 is heat-treated.
[0028] The LGPS-type solid electrolyte of the present invention obtained as described above can be formed into a desired molded body by various means and used in various applications including the all-solid-state battery described below. The molding method is not particularly limited. For example, the same molding method as the molding method for each layer constituting the all-solid-state battery described in <All-solid-state battery> described later can be used.
[0029] <All-solid-state battery> The LGPS-type solid electrolyte of the present invention can be used, for example, as a solid electrolyte for an all-solid-state battery. According to a further embodiment of the present invention, there is provided an all-solid-state battery comprising the above-mentioned solid electrolyte for an all-solid-state battery.
[0030] Here, the "all-solid-state battery" refers to an all-solid-state lithium-ion secondary battery. FIG. 2 is a schematic cross-sectional view of an all-solid-state battery according to one embodiment of the present invention. The all-solid-state battery 10 has a structure in which a solid electrolyte layer 2 is disposed between a positive electrode layer 1 and a negative electrode layer 3. The all-solid-state battery 10 can be used in various devices including mobile phones, personal computers, and automobiles.
[0031] The LGPS type solid electrolyte of the present invention may be contained as a solid electrolyte in at least one of the positive electrode layer 1, the negative electrode layer 3, and the solid electrolyte layer 2. When the LGPS type solid electrolyte of the present invention is contained in the positive electrode layer 1 or the negative electrode layer 3, the LGPS type solid electrolyte of the present invention is used in combination with a known positive electrode active material or negative electrode active material for lithium ion secondary batteries. The amount ratio of the LGPS type solid electrolyte of the present invention contained in the positive electrode layer 1 or the negative electrode layer 3 is not particularly limited. The LGPS type solid electrolyte of the present invention may be composed of a single electrolyte, or may be composed of an oxide solid electrolyte (e.g., Li7La3Zr2O 12 ), sulfide-based solid electrolytes (e.g., Li2S-P2S5), and other complex hydride solid electrolytes (e.g., LiBH4, 3LiBH4-LiI), etc., may be used in appropriate combination.
[0032] The all-solid-state battery is produced by forming and laminating each of the layers described above, but there are no particular limitations on the method for forming and laminating each layer.
[0033] For example, there are a method in which a solid electrolyte and / or an electrode active material is dispersed in a solvent to form a slurry, which is then applied by a doctor blade or spin coating, and then rolled to form a film; a gas phase method in which a film is formed and laminated using a vacuum deposition method, an ion plating method, a sputtering method, a laser ablation method, or the like; and a pressure molding method in which powder is molded by hot pressing or cold pressing without applying heat, and then laminated.
[0034] Since the LGPS-type solid electrolyte of the present invention is relatively soft, it is particularly preferable to form and stack each layer by pressure molding to produce an all-solid-state battery. As the pressure molding method, there are hot pressing performed with heating and cold pressing performed without heating, but cold pressing can also be used to sufficiently mold the electrolyte.
[0035] The present invention also includes a molded body obtained by hot-molding the LGPS-type solid electrolyte of the present invention. The molded body is suitably used as an all-solid-state battery. The present invention also includes a method for producing an all-solid-state battery, which includes a step of hot-molding the LGPS-type solid electrolyte of the present invention. EXAMPLES
[0036] The present embodiment will be described in more detail below with reference to examples, but the present embodiment is not limited to these examples. In addition, the moisture content in the nitrogen gas used in the following Examples and Comparative Examples was measured using a dew point meter (TK-100 online dew point meter manufactured by Techne Measurement Co., Ltd.).
[0037] (Example 1) (Manufacture of Ge-type LGPS Precursor) In a glove box under an argon atmosphere, Li2S (manufactured by Sigma-Aldrich, purity 99.8%), P2S5 (manufactured by Sigma-Aldrich, purity 99%), and GeS2 (manufactured by Sigma-Aldrich, purity 99%) were weighed out so as to have a molar ratio of Li2S:P2S5:GeS2 = 5:1:1 and preliminarily mixed in an agate mortar. Next, the preliminarily mixed raw materials were put into a 45 mL zirconia pot, and further zirconia balls (「YTZ」manufactured by Nikkato Corporation, φ10 mm, 15 pieces) were put in, and the pot was completely sealed. This pot was attached to a planetary ball mill (「P-7」manufactured by Fritsch) and mechanically milled at a rotational speed of 500 rpm for 10 hours to obtain a Ge-type LGPS precursor. (Firing of Ge-type LGPS Precursor) The obtained precursor was fired using the heating container 11 shown in Fig. 7. In a glove box under an argon atmosphere, 0.5 g of the precursor was put into the glass inner cylinder 12 and installed in the tubular furnace 16 so that the precursor was not exposed to the atmosphere. After replacing the gas in the heating container 11 from argon gas to nitrogen gas (moisture content 145 ppm), while blowing nitrogen gas (moisture content 145 ppm), the temperature was raised to 550 °C over 3 hours, and then fired at 550 °C for 8 hours to obtain a Ge-type LGPS solid electrolyte.
[0038] (Example 2) (Manufacture of Ge-type LGPS Precursor) The same operation as in Example 1 was performed to obtain a Ge-type LGPS precursor. (Firing of Ge-type LGPS Precursor) The same operation as in Example 1 was performed except that the moisture content of the nitrogen gas was set to 203 ppm to obtain a Ge-type LGPS solid electrolyte.
[0039] (Example 3) <Manufacture of Ge-type LGPS Precursor> The same operations as in Example 1 were carried out to obtain a Ge-type LGPS precursor. <Firing of Ge-type LGPS Precursor> The same operations as in Example 1 were carried out except that the moisture content of the nitrogen gas was 289 ppm, to obtain a Ge-type LGPS solid electrolyte.
[0040] (Example 4) <Manufacture of Ge-type LGPS Precursor> The same operations as in Example 1 were carried out to obtain a Ge-type LGPS precursor. <Firing of Ge-type LGPS Precursor> The same operations as in Example 1 were carried out except that the moisture content of the nitrogen gas was 123 ppm, to obtain a Ge-type LGPS solid electrolyte.
[0041] (Comparative Example 1) <Manufacture of Ge-type LGPS Precursor> The same operations as in Example 1 were carried out to obtain a Ge-type LGPS precursor. <Firing of Ge-type LGPS Precursor> The same operations as in Example 1 were carried out except that the moisture content of the nitrogen gas was 23 ppm, to obtain a Ge-type LGPS solid electrolyte.
[0042] (Example 5) <Manufacture of Sn-type LGPS Precursor> In a glove box under an argon atmosphere, Li2S (manufactured by Sigma-Aldrich, purity 99.8%), P2S5 (manufactured by Sigma-Aldrich, purity 99%), and SnS2 (manufactured by High Purity Chemical Co., Ltd.) were weighed so as to have a molar ratio of Li2S:P2S5:SnS2 = 5:1:1 and preliminarily mixed in an agate mortar. Next, the preliminarily mixed raw materials were put into a 45 mL zirconia pot, and further zirconia balls (manufactured by Nikkato Co., Ltd. "YTZ", φ10 mm, 15 pieces) were put in, and the pot was completely sealed. This pot was attached to a planetary ball mill (manufactured by Fritsch "P-7") and mechanically milled at a rotational speed of 800 rpm for 10 hours to obtain a Sn-type LGPS precursor. <Firing of Sn-type LGPS Precursor> The obtained precursor was fired using the heating container 11 shown in Fig. 7. In a glove box under an argon atmosphere, 0.5 g of the precursor was placed in the glass inner cylinder 12 and installed in the tubular furnace 16 so that the precursor was not exposed to the atmosphere. After replacing the gas in the heating container 11 from argon gas to nitrogen gas (water content 145 ppm), while blowing nitrogen gas (water content 145 ppm), the temperature was raised to 550 °C over 3 hours, and then fired at 550 °C for 8 hours to obtain an Sn-type LGPS solid electrolyte.
[0043] (Example 6) <Production of Sn-type LGPS Precursor> The same operation as in Example 5 was performed to obtain an Sn-type LGPS precursor. <Firing of Sn-type LGPS Precursor> The same operation as in Example 5 was performed except that the water content of the nitrogen gas was 203 ppm to obtain an Sn-type LGPS solid electrolyte.
[0044] (Example 7) <Production of Sn-type LGPS Precursor> The same operation as in Example 5 was performed to obtain an Sn-type LGPS precursor. <Firing of Sn-type LGPS Precursor> The same operation as in Example 5 was performed except that the water content of the nitrogen gas was 289 ppm to obtain an Sn-type LGPS solid electrolyte.
[0045] (Example 8) <Production of Sn-type LGPS Precursor> The same operation as in Example 5 was performed to obtain an Sn-type LGPS precursor. <Firing of Sn-type LGPS Precursor> The same operation as in Example 5 was performed except that the water content of the nitrogen gas was 123 ppm to obtain an Sn-type LGPS solid electrolyte.
[0046] (Comparative Example 2) <Production of Sn-type LGPS Precursor> The same operation as in Example 5 was performed to obtain an Sn-type LGPS precursor. <Firing of Sn-Type LGPS Precursor> The same operations as in Example 5 were carried out except that the moisture content of nitrogen gas was set to 23 ppm, and an Sn-type LGPS solid electrolyte was obtained.
[0047] <Measurement of Lithium Ion Conductivity> The LGPS-type solid electrolytes obtained in Examples 1 to 8 and Comparative Examples 1 and 2 were subjected to uniaxial pressing (420 MPa) to obtain disks with a thickness of about 1 mm and a diameter of 10 mm. Using an all-solid-state battery evaluation cell (manufactured by Hokuen Co., Ltd.), alternating current impedance measurement (Solartron's "SI1260 IMPEDANCE / GAIN-PHASE ANALYZER") was performed at room temperature (25°C) by the four-terminal method to calculate the lithium ion conductivity. Specifically, after placing the sample in a thermostat set at 25°C and holding it for 30 minutes, the lithium ion conductivity was measured. The measurement frequency range was 0.1 Hz to 1 MHz, and the amplitude was 50 mV. The measurement results of the lithium ion conductivity are shown in Fig. 3 (Ge-type LGPS solid electrolyte) and Fig. 4 (Sn-type LGPS solid electrolyte). From Fig. 3 (Ge-type LGPS solid electrolyte), Examples 1 to 4 with a higher moisture content in nitrogen gas showed higher ion conductivity compared to Comparative Example 1 with a lower moisture content in nitrogen gas. This is presumably because the moisture in nitrogen gas reacted with the solid electrolyte surface and oxygen was incorporated into the structure, changing the size of the tunnels through which Li ions in the crystal pass to a size more conducive to conduction. Also, Fig. 4 (Sn-type LGPS solid electrolyte) shows the same ion conductivity behavior as Fig. 3 (Ge-type LGPS solid electrolyte).
[0048] <Measurement of X-ray Diffraction> For the LGPS-type solid electrolytes obtained in Examples 1 to 8 and Comparative Examples 1 and 2, X-ray diffraction measurement (PANalytical's "X'Pert3 Powder", CuKα: λ = 1.5405 Å) was performed at room temperature (25°C) under an Ar atmosphere. As shown in the results of the X-ray diffraction measurements in Figs. 5 and 6, in Examples 1 to 8 and Comparative Examples 1 and 2, diffraction peaks were observed at least at 2θ = 20.18° ± 0.50°, 20.44° ± 0.50°, 26.96° ± 0.50°, and 29.58° ± 0.50°. This pattern corresponds to the Li 10 GeP2S 12 This confirmed that the compound had an LGPS-type crystal structure. [Explanation of symbols]
[0049] 1 Positive electrode layer 2 Solid electrolyte layer 3. Negative electrode layer 10 All-solid-state battery 11 Heating container 12 Glass inner cylinder 13 Glass outer cylinder 14 LGPS type solid electrolyte precursor 15 Thermocouple 16 Tube furnace
Claims
1. A method for producing an LGPS type solid electrolyte, comprising the step of firing an LGPS type solid electrolyte precursor in a nitrogen gas atmosphere containing moisture in the range of more than 100 ppm and not more than 300 ppm.
2. 2. The method for producing an LGPS type solid electrolyte according to claim 1, wherein the LGPS type solid electrolyte has peaks at least at positions of 2θ=20.18°±0.50°, 20.44°±0.50°, 26.96°±0.50°, and 29.58°±0.50° in X-ray diffraction (CuKα: λ=1.5405 Å).
3. 3. The method for producing an LGPS type solid electrolyte according to claim 1, wherein the firing temperature is 200° C. to 700° C.
4. 4. The method for producing an LGPS type solid electrolyte according to claim 1, wherein the LGPS type solid electrolyte contains Ge and has an ionic conductivity of 3.2 mS / cm or more at 25° C.
5. 4. The method for producing an LGPS type solid electrolyte according to claim 1, wherein the LGPS type solid electrolyte contains Sn and has an ionic conductivity of 2.8 mS / cm or more at 25° C.
Citation Information
Patent Citations
Sulfide-based lithium ion-conductive solid electrolyte and synthesis thereof
JP1994279050A
Coating positive electrode active material
JP2020181638A
Sulfide-based lithium-ion conductive solid electrolyte and method for synthesizing the same
JP3125507B2
Method for producing LGPS-based solid electrolyte
WO2019044517A1
LGPS-based solid electrolyte and production method
WO2019239949A1